(De-)Politicising women's collective action: international actors and land inheritance in post-war Burundi. Issue 149 (2nd July 2016) - Saiget, Marie
Abstract : This article focuses on women's collective action promoting land inheritance in Burundi. It aims to discuss the role of international actors in social transformations, questioning to what extent they have shaped women's collective action since the 1970s, in particular since the country's president took the official decision to stop the legislative and political process for adopting a law in 2011. The article argues that international actors are a central factor in (de-)politicisation by playing the role of a third party in the relationship between women's associations and the state. These interactions produce a particular form of mobilisation that promotes law as a tool to build, frame and provide answers to the land issue.